MOTIVASI BELAJAR SISWA SMA NEGERI 1 PADANG BOLAK DI ERA DIGITAL: ANTARA TANTANGAN DAN PELUANG - Siregar, Rajiun; Adinda, Anita (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
The development of digital technology has significantly transformed the field of education, particularly at thesenior high school level. On one hand, technology offers great potential to enhance student learning motivationthrough broad access to information, interactive media, and flexible learning schedules. On the other hand,digital disruption also presents challenges such as social media distractions, visual fatigue, and unequalaccess to technology. This study aims to identify the factors that influence students’ learning motivation in thedigital era and formulate strategies to optimize the use of technology in education. Employing a descriptivequantitative approach, a survey was conducted involving 72 science-track students at SMA Negeri 1 PadangBolak. The ARCS model (Attention, Relevance, Confidence, Satisfaction) served as the analytical frameworkto assess student motivation. The results show that 70.8% of students reported increased motivation with theaid of digital technology, especially in the areas of attention and satisfaction. However, 55.5% admitted beingdistracted by social media, while 48.6% experienced fatigue due to prolonged screen exposure. The studyrecommends the integration of technology-based pedagogy, the strengthening of digital literacy, andproportional supervision of digital device use to foster effective, meaningful, and motivating learningexperiences